(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This study on logistics focused on the procurement and vendor portal system information to solve the problems encountered to take advantage of the ordered item and find solicit, active vendor management to bid based the all-department requests and purposes to purchase business goods and equipment items agreement process because of the well-provided structures between procurement and vendor portal transactions. Thus, from now, the use of technology is the one of effective strategies in logistics. The project of procurement and vendor Portal combined the transactions and are very effective useful inside the part of the logistics department. Agile scrum methodology was used here. The scrum master, scrum team developers, and scrum collaborated in this agile development project. It is composed of project background, project charter, product backlog, sprint backlog, sprint burndown chart, user manual, recommendation, and conclusion and appendices. It discussed the module problem, solution, and output in the system. The developers’ findings are very crucial because it is difficult to resolve different issues in Logistic 2, such as data structures and integrations transactions. The problem with our system in Logistic 2 was the lack of tables and different transaction situation reports. The problem of warehousing and procurement is the lack of tables for inventory and reports to print and purchase orders. This study is important for the user/staff to know the procurement and vendor portal to resource process and be guided in transactions. It serves as a user manual from the system that was developed by the proponents. The objectives are the goal that should be reached by the team. Objectives are also essential for developing a project. This project study may have some loopholes in terms of the functionality of the system, but it has standard functionality and is well-documented in terms of process.